DIAGNOSTIC ASSESSMENT IN INDONESIAN LANGUAGE LEARNING (CASE STUDY AT SMP NEGERI 1 WATAN SOPPENG, LALABATA DISTRICT, SOPPENG REGENCY) - Asriani; Syahruddin; Aliem Bahri (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to describe the implementation of diagnostic assessments in Indonesian language learning at SMP Negeri 1 Watansoppeng, Lalabata District, Soppeng Regency, as well as identify the obstacles faced by teachers in implementing diagnostic assessments in accordance with the principles of the Independent Curriculum. This study also examines the factors that affect the success of the implementation of diagnostic assessments in the school. The method used in this study is a qualitative approach with a descriptive design. Data was collected through observations, interviews, and questionnaires to the teachers and students involved. Data analysis was carried out thematically to obtain a holistic picture of the implementation of diagnostic assessments. The results of the study show that the implementation of diagnostic assessments at SMP Negeri 1 Watansoppeng is in accordance with the principles of the Independent Curriculum, although there are still some challenges. The main obstacles faced by teachers include the diversity of students' abilities, limited facilities and infrastructure, and teachers' inadequate understanding of diagnostic assessments. Factors that affect the implementation of diagnostic assessments include teacher readiness, school support, large number of students, and the diversity of student learning styles. This study suggests that more intensive training for teachers be carried out and the improvement of facilities that support diagnostic assessments so that the implementation of assessments is more effective and in accordance with the needs of students.